Micromorphology characterization of crystal calcium carbonate and exopolysaccharides quantification carbonatogenic bacterial LTP4-d isolated from historical painting of Maros-Pangkep karst area, Indonesia - NUR AFIFAH ZHAFIRAH; NUR HAEDAR; SLAMET SENTOSA; FUAD GANI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Zhafirah NA, Haedar N, Sentosa S, Gani F. 2024. Micromorphology characterization of crystal calcium carbonate and exopolysaccharides quantification carbonatogenic bacterial LTP4-d isolated from historical painting of Maros-Pangkep karst area, Indonesia. Biodiversitas 25: 2139-2147. Indonesia possesses the second-largest limestone/karst region globally, trailing only China. Among Indonesia’s limestone region, the Maros-Pangkep karst area in South Sulawesi stands out which obtained prehistoric rock art dating back at least 45.5 thousand years ago. However, over time, those paintings have begun to deteriorate due to many causes, one of which caused by overlayering of the deposition of calcium carbonate precipitates covering the surface of the paintings. This can occur due to the presence of microorganism with the ability to precipitate calcium carbonate on the surface of those paintings. Microorganism that have the ability to precipitate calcium carbonate are usually known as carbonatogenic bacteria or ureolytic bacteria. This study aimed to isolate the carbonatogenic bacteria and then assess how effectively it precipitates calcium carbonate, also to determine the production of EPS and characteristic micro-morfology of CaCO3 produced by carbonatogenic bacteria isolated from historical painting of Maros-Pangkep karst, Indonesia. Results showed that sixty bacterial isolates were successfully isolated from prehistoric paintings in Maros-Pangkep karst, which 24 isolates were confirmed as carbonatogenic bacteria. The highest amount of CaCO3 precipitate was recorded from LTP4-d isolates which able to precipitate 37.62±0.12 mgmL-1 calcium carbonate. The highest amounts of ammonia and EPS production were also from LTP4-d. The SEM results showed that CaCO3 precipitate from LTP4-d has a type of vaterite with element contents including C 0.32%; O 15.24%; Ca 84.53%. This study presents novel findings on the capability of carbonatogenic bacteria from prehistoric paintings in Maros-Pangkep karst to induce calcium carbonate precipitation which can be utilized as a reference for repairing and preserving prehistoric paintings found in the Maros-Pangkep karst area.